GEO- AND COSMOCHEMISTRY OF THE TWIN ELEMENTS YTTRIUM AND HOLMIUM - Pack A.; van Zuilen M.; Russell S.S.; Shelley J.M.G. (My University, 2007)
We have analyzed the Y/Ho-ratios in bulk chondrites, chondrules and four Ca- and Al-rich inclusions (CAIs) from carbonaceous and unequilibrated ordinary and enstatite chondrites (EC) by laser ablation inductively coupled mass spectrometry (LA-ICPMS). We demonstrate that bulk rock sample preparation by containerless melting is a suitable method for preparation of bulk rock samples for high-precision LA-ICPMS. Bulk chondrites have variable Y/Ho-ratios. Carbonaceous chondrites (CI1, CM2, CV3, and CK4) have a common Y/Ho-ratio (25.94 ± 0.08, 2σ) that is regarded as the solar system Y/Ho-ratio. The Y/Ho-ratio increases from carbonaceous, through ordinary (LL, L, H) to enstatite chondrites (EL6), which show the highest Y/Ho-ratio of 27.25. We discuss the result with respect to the origin of fractionation of Re and Os between chondrite groups. Within analytical error, Y and Ho show a good correlation in OC and CV3 chondrules and define an Y/Ho-ratio of 26.22 ± 0.40 (2σ). Y/Ho-fractionation in Ca- and Al-rich inclusions is related to differences in volatility. The bulk silicate Earth is suggested to have a solar Y/Ho-ratio and links the Earth with carbonaceous chondrites. Y/Ho variations in primitive and differentiated terrestrial igneous rocks are discussed in framework of incompatibility of Y and Ho during partial melting. Applicability of Y/Ho as tracer for or against a sedimentary origin of the putative host rock of the Earth's oldest traces of life from the island of Akilia is briefly discussed. © 2007.